TECHNOLOGY FOR FOUR SKILLS ARABIC IN THE ERA EMERGENCY OF COVID-19 IN INDONESIA - Febriani, Suci Ramadhanti; Anasruddin, Anasruddin (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
The integration of technology and learning has become the primary key in developing various Arabic learning models in emergencies of the COVID-19 era. This study aims to describe and uncover the impact of technology on the learning process of Arabic on four Arabic language skills. This research uses a qualitative approach design utilizing the case study research method. Data obtained through observation techniques, interviews, and documentation with data analysis techniques using the theory of Milles and Huberman. The results revealed that the impact of technology on learning Arabic included several aspects of innovation in curriculum planning, implementation of learning, strategy development, and evaluation that varied online. The findings of this study are that the integration of technology with Arabic learning can improve creative and critical thinking processes and form a constructivist mindset. This study recommends that the use of appropriate technology for four language skills will affect Arabic learning outcomes to the maximum.